Risk Based Bank Rating dalam Mengukur Tingkat Kesehatan Perbankan - Indrianasari, Neny Tri; Ifa, Khoirul (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2019)
The Financial Services Authority assesses the national banking industry in the better shape shown by some indicators, one of which the involvement of the Government in realizing economic growth. With the better banking conditions will marimbas Bank on growth Of Islamic Peoples. This research aims to know the level of health of bank Syariah BPR in East Java by using methods of Risk-Based Bank Rating. The assessment by the method of Risk-Based Bank Rating consists of four factors of risk profile, Good Corporate Governance, earning and capital of each bank. This research uses descriptive method quantitative approach to analyze the ratio-the ratio of the measured. The data type used is the time series data of the year 2015 – 2017. Source data obtained from the Financial Services Authority website (OJK). Data analysis techniques using analysis of Risk-Based Bank Rating (RBBR) consist of four-factor risk profile, Good Corporate Governance, earning and capital. The study concluded that the overall average value of NPF Bank Of Islamic People (BPRS) of 13.37% unhealthy, with an average overall rating Of Sharia Rural Banks ROA (BPRS) of 0.11% with the predicate less healthy and that the average overall rating Of Sharia Rural Banks CAR (BPRS) amounted to 28.47% with very healthy.